Sex, drugs and smart phone applications: findings from semistructured interviews with men who have sex with men diagnosed with Shigella flexneri 3a in England and Wales. (28th April 2015) - Gilbart, V L; Simms, I; Jenkins, C; Furegato, M; Gobin, M; Oliver, I; Hart, G; Gill, O N; Hughes, G
Abstract : Objectives: To inform control strategies undertaken as part of an outbreak of Shigella flexneri 3a among men who have sex with men (MSM). Methods: All men aged ≥18 years diagnosed with S flexneri 3a between October 2012 and May 2013 were invited to participate. Semistructured in-depth quantitative interviews were conducted to explore lifestyle and sexual behaviour factors. Results: Of 53 men diagnosed, 42 were interviewed of whom 34 were sexually active MSM. High numbers of sexual partners were reported (median=22) within the previous year; most were casual encounters met through social media networking sites (21/34). 63% (20/32) were HIV-positive and actively sought positive partners for condomless sex. 62% (21/34) of men had used chemsex drugs (mephedrone, crystal methamphetamine and γ-butyrolactone/γ-hydroxybutrate), which facilitate sexually disinhibiting behaviour during sexual encounters. 38% (8/21) reported injecting chemsex drugs. Where reported almost half (12/23) had attended or hosted sex parties. All reported oral–anal contact and fisting was common (16/34). Many had had gonorrhoea (23/34) and chlamydia (17/34). HIV-positive serostatus was associated with both insertive anal intercourse with a casual partner and receptive fisting (adjusted OR=15.0, p=0.01; adjusted OR=18.3, p=0.03) as was the use of web applications that promote and facilitate unprotected sex (adjusted OR=19.8, p=0.02). Conclusions: HIV-positive MSM infected with S flexneri 3a used social media to meet sexual partners for unprotected sex mainly at sex parties. The potential for the transmission of S flexneri, HIV and other infections is clear. MSM need to be aware of the effect that chemsex drugs have on their health.